(untitled) (Fiep Bulletin - online, 2013)
The blood lactate increases the extent that it increases the intensity of the exercise. The synthesis of ammonia also has its own kinetic and its implications for the muscular fatigue and the physical performance. The proposal of this study was to evaluate the effects of chronic supplementation of glutamine on the levels of blood lactate and ammonia in rats submitted to aerobic exercise in swimming. 24 rats were used, male, in four groups, sedentary, sedentary supplemented with glutamine, trained and trained supplemented with glutamine. Having been familiar with the liquid medium and with weights tied to the tail, the animals were subjected to two weeks of training, and five days a week, 60 minutes per day or until exhaustion. The workload ranged in a ratio of 2% to 5% of body mass. On the last day the animals trained until exhaustion then were anesthetized and had their blood collected. The values of lactate and ammonia did not show significant differences when confronted between the four groups. The results of this study say that enable the addition of chronic glutamine did not alter the response of lactate, while for ammonia observed that the glutamine not provided protection against amonemia in GSE and GTRE, which showed higher levels of this metabolite, but have not made significant differences.